Trend and early outcomes in isolated surgical aortic valve replacement in the United Kingdom - Chan, Jeremy; Dimagli, Arnaldo; Fudulu, Daniel P.; Sinha, Shubhra; Narayan, Pradeep; Dong, Tim; Angelini, Gianni D. (Frontiers in Cardiovascular Medicine, 2023)
Surgical aortic valve replacement (SAVR) is traditionally the gold standard treatment in patients with aortic valve disease. The advancement of transcatheter aortic valve replacement (TAVR) provides an alternative treatment to patients with high surgical risks and who had previous cardiac surgery. We aim to evaluate the trend; early clinical outcomes, and the choice of prosthesis use in isolated SAVR in the United Kingdom. All patients (n= 79173) who underwent elective or urgent isolated surgical aortic valve replacement (SAVR) from 1996 to 2018 were extracted from the National Adult Cardiac Surgery Audit database. Patients who underwent additional procedures and emergency or salvage SAVR, were excluded from the study. Trend and clinical outcomes were investigated in the whole cohort. Patients who had previous cardiac surgery, high risk groups (EuroScore II >4%) and predicted/observed mortality were evaluated. Furthermore, use of biological prostheses in 5 different age groups: <50, 50-59, 60-69, 70-79 and >80 were investigated. Clinical outcomes between the use of mechanical and biological aortic valve prosthesis in patients < 65 years old were analysed using propensity score matching. The number of isolated SAVR increased across the study period with an average of 4661 cases performed annually after 2010. The in-hospital/30-day mortality rate decreased from 5.28% (1996) to 1.06% (2018), despite an increasing trend in EuroScore II. The number of isolated SAVR performed in octogenarians increased from 596 in 2007 (the first year when TAVR was introduced in the UK) to 872 in 2015, then progressively decreased to 681 in 2018. Biological prosthesis usage increased across all age group, and particularly in the 60-69 group, from 24.59% (1996) to 81.87% (2018). There was no differences in short term outcomes in patients <65 years old received a biological or mechanical prostheses after propensity score matching. SAVR remains an effective treatment for patients with isolated aortic valve disease with a low 30-day mortality rate. The number of high-risk patients and octogenarians undergone isolated SAVR and those requiring redo surgery has reduced since 2016, likely due to the advancement in TAVR. The use of biological aortic prostheses has increased significantly in recent years.